DUSP22 Ameliorates Endothelial-to-Mesenchymal Transition in HUVECs through Smad2/3 and MAPK Signaling Pathways - Lu Chen; Hongyu Su; Zekai Tao; Cui Liang; Zhongzhao Liu; Yiming Dong; Peipei Zheng; Yuan Liu (Hindawi-Wiley, 2024)
Endothelial-to-mesenchymal transition (EndMT) is the process by which endothelial cells lose their endothelial properties and acquire mesenchymal characteristics. Dual-specific protein phosphatase 22 (DUSP22) inactivates various protein kinases and transcription factors by dephosphorylating serine/threonine residues: hence, it plays a key role in many diseases. The aim of this study was to explore the functional role of DUSP22 in EndMT. In the transforming growth factor-β-induced EndMT model in human umbilical vein endothelial cells (HUVECs), we observed a downregulation of DUSP22 expression. This DUSP22 deficiency could aggravate EndMT. Conversely, the overexpression of DUSP22 could ameliorate EndMT. We used signaling pathway inhibitors to verify our results and found that DUSP22 could regulate EndMT through the smad2/3 and the mitogen-activated protein kinase (MAPK) signaling pathways. In summary, DUSP22 ameliorates EndMT in HUVECs in vitro through the smad2/3 and MAPK signaling pathways.